1995
DOI: 10.1105/tpc.7.10.1713
|View full text |Cite
|
Sign up to set email alerts
|

The stroma of higher plant plastids contain ClpP and ClpC, functional homologs of Escherichia coli ClpP and ClpA: an archetypal two-component ATP-dependent protease.

Abstract: A cDNA representing the plastid-encoded homolog of the prokaryotic ATP-dependent protease ClpP was amplified by reverse transcription-polymerase chain reaction, cloned, and sequenced. ClpP and a previously isolated cDNA designated ClpC, encoding an ATPase related t o proteins encoded by the ClpA/S gene family, were expressed in Eschefichia coli. Antibodies directed against these recombinant proteins recognized proteins in a wide variety of organisms. N-terminal analysis of the Clp protein isolated from crude l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 50 publications
(52 reference statements)
6
140
0
1
Order By: Relevance
“…Chloroplasts, consistent with their endosymbiotic origin, contain various proteases of bacterial ancestry Clarke et al, 2005). One of the first identified was the ATPdependent Clp protease localized primarily in the stroma (Shanklin et al, 1995). The model for the Ser-type Clp protease has long been the one in Escherichia coli, which consists of a proteolytic core flanked on one or both sides by a HSP100 molecular chaperone.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplasts, consistent with their endosymbiotic origin, contain various proteases of bacterial ancestry Clarke et al, 2005). One of the first identified was the ATPdependent Clp protease localized primarily in the stroma (Shanklin et al, 1995). The model for the Ser-type Clp protease has long been the one in Escherichia coli, which consists of a proteolytic core flanked on one or both sides by a HSP100 molecular chaperone.…”
Section: Introductionmentioning
confidence: 99%
“…Double knockout of both genes causes lethality, indicating that Hsp93 is essential (Kovacheva et al, 2007). In addition, Hsp93 has been proposed to act as a regulatory subunit of the ClpP protease in chloroplasts (Shanklin et al, 1995;Desimone et al, 1997;Sokolenko et al, 1998;Halperin et al, 2001). Interestingly, although Hsp93 was not detected in the ClpP core complex isolated from chloroplasts, the land plant chloroplast ClpP complex contains two additional peripheral subunits, ClpT1 and ClpT2 (previously named ClpS1 and ClpS2), that have high sequence similarity to the N-terminal portion of Hsp93 (Peltier et al, 2004).…”
mentioning
confidence: 99%
“…We recently found that a ClpC1 subunit of the chloroplast Clp protease is involved in the regulation of CAO [25]. Since the ClpC1 subunit is a chaperone that recognizes the protease substrate sequences [31,32], it is tempting to speculate that the ClpC1 recognizes the A domain directly in a chlorophyll-b dependent manner. Nevertheless, the involvement of other types of proteases or other factors should not be excluded since mutation in the ClpC1 gene did not abolish the full regulation of the CAO protein levels [25].…”
Section: Discussionmentioning
confidence: 99%